Design of a Bidirectional Antenna inside a Vehicle and Measurement of Power Link for Vehicle-to-Vehicle Communication at 5.8 GHz - Soon-Soo Oh; Dong-Woo Kim; Se-Woong Na; Jin-Dae Kim; Wook-Ki Park (International Journal of Antennas and Propagation)
Communication between moving vehicles is very important for safety. In this paper, a bidirectional antenna that can be installed inside a vehicle is proposed and tested in a real vehicular environment at 5.8 GHz. The forward link and backward link seated by two persons and three persons were compared in terms of received RF power and the peak-to-average power ratio (PAR). It was found that, even with three persons, the power link fulfilled the communication requirements using the proposed antenna.